PERLUASAN KEWENANGAN BPK DALAM MENGAWASI KEUANGAN NEGARA DI LINGKUP PEMERINTAHAN DAERAH - Habibi, Dani; Hermawan, Ian Aji (Veritas et Justitia, 2020)
State budget management is tightly related to how the existing state law regulates fiscal relationship between the central government and the regional-local governments.  The authority granted to regional-local government to manage their own budgeting more or less autonomously in practice results in mismanagement, misuse of available financial resources and even corruption.  Unfettered and unchecked financial leakage at the regional government level may and have resulted in failure to realize and implement projects much needed by society.  In light of this situation, a justified need arise for state intervention to monitor-control planning and realization of regional-local government budget. The author proposed the expansion of the Audit Board of the Republic Indonesia’s authority. They should not passively wait for financial reports to be submitted but actively assist regional-local government in planning their own budget, monitor the spending and realization of it and lastly, provide assistance in drafting the final report.